Towards to Psychological-based Recommenders Systems: A survey on Recommender Systems - Nunes, Maria Augusta Silveira Netto (Scientia Plena, 2010)
<!--StartFragment--><span style="font-size: 10.0pt; font-family: "Times New Roman"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-language: EN-US;" lang="EN-GB">This paper describes a brief survey of Psychological-based Recommender System describing the state of the art of the area. Firstly we briefly define the Recommender Systems, followed by the description of the approaches usually used in order to implement them. Next, we present the strengths and weaknesses of the recommendation techniques, followed by some examples. Next, we present the preliminary work developed considering Psychological-based Recommender Systems. In this paper we detail an experiment illustrating the scenario where we apply a Personality-based Recommender System. Finally we present some conclusions.<!--EndFragment-->